The Israel-Palestine Sovereignty Struggle: A Historical Review Based On Territorial Claims - Pratama, Affilah Putra; Wiratama, Nara Setya; Budiono, Heru (History Education, University of Jember, 2023)
The land of Palestine is holy land for the three major religions, namely Islam, Christianity and Judaism. Israel and Palestine are countries that claim that this land is their territory, so this has sparked a prolonged conflict between the two. This research aims to provide an overview of the history of territorial claims in the Israeli-Palestinian region, territorial claims based on an Israeli-Palestinian perspective, and efforts to resolve the Israeli-Palestinian conflict. Researchers use the historical method with a qualitative approach, which has stages of heuristics, criticism, interpretation and historiography. The research results concluded that the Israeli-Palestinian conflict is a complex problem. The involvement of religious, political and historical dimensions in it can influence a person's views and understanding of the Israeli-Palestinian territorial claims. Through this research, it can be seen that the importance of good diplomacy and mediation can encourage the creation of commitment and trust in each other, thereby creating a sense of tolerance which can be used as the key to fair sovereignty for both parties. Keywords: Israel, Palestine, Islam, Judaism